A solution for fully developed turbulent heat transfer in a circular tube with uniform wall temperature, using a continuous velocity profile - Merttürk, İbrahim. (Thesis (M.S.) - Robert College. Faculty of Graduate School of Engineering, 1970., 1970)
Heat transfer coefficients and temperature profiles for fully developed turbulent pipe flow with uniform wall temperature are predicted for P 1. The continous and differentiable velocity profile of Pai (1)1 is used to integrate the energy equation numerically. Turbulent pipe flow is assumed to be steady, and thermally and hydrodynamically fully developed. The ratio of the eddy diffusivities is taken to be unity. Axial conduction is neglected, and the flow is assumed to be axisymmetric with constant fluid properties. The results obtained are presented as curves and tables. Three correlating equations are given which predict the Nusselt number for liquid-metals and for gases.
Keywords: Heat -- Transmission -- Mathematical models.; Turbulence.; Tubes -- Fluid dynamics.